2020
DOI: 10.1021/acssensors.0c00593
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Digital MicroRNA Detection Using Cross-Inhibitory DNA Circuits

Abstract: Ubiquitous post-transcriptional regulators in eukaryotes, microRNAs are currently emerging as promising biomarkers of physiological and pathological processes. Multiplex and digital detection of microRNAs represents a major challenge toward the use of microRNA signatures in clinical settings. The classical reverse transcription polymerase chain reaction quantification approach has important limitations because of the need for thermocycling and a reverse transcription step. Simpler, isothermal alternatives have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Here we decided to replace the B11 output of the psT with the complementary sequence antiB11 (aB11). For clarity we named these repressing input modules protein sensing killer Template (pskT), in line with recently described killer Templates (kT) ( 25 ) (Figure 2C , E ). At the same time, the mixture was complemented with an unconditional mechanism to produce the signal B11, which we call a source template (sT).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Here we decided to replace the B11 output of the psT with the complementary sequence antiB11 (aB11). For clarity we named these repressing input modules protein sensing killer Template (pskT), in line with recently described killer Templates (kT) ( 25 ) (Figure 2C , E ). At the same time, the mixture was complemented with an unconditional mechanism to produce the signal B11, which we call a source template (sT).…”
Section: Resultsmentioning
confidence: 92%
“…We started with the PEN-DNA framework ( 22 ), a powerful molecular programming language which has allowed the rational building of a variety of molecular systems, including batch oscillators ( 23 ), programmable pattern formation ( 24 ), or ultrasensitive multi-input sensors ( 25 ). The PEN-DNA employs Polymerase, Exonuclease and Nickase (PEN) enzymes as the chemical machinery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since multiplexing capability plays a crucial role in miRNAs detection, in addition to the abovementioned multiplexing approaches, it is worth citing the suspension arrays (i.e., on-particle), which represent promising emerging methods for highly multiplex analysis of complex samples due to the versatility of the encoded microspheres used in conjunction with flow cytometry [133]. Furthermore, Rondelez et al recently reported an isothermal amplification mechanism for multiplex and digital detection of miRNAs using the rational building of a molecular circuit that suppresses non-specific amplification due to cross-talk reactions [134]. In conclusion, extensive efforts have been made so far to develop efficient and sensitive methods for miRNA detection, but there still remains a need for a standardized method that should be highly sensitive, specific and multiplexable.…”
Section: Mirna Profiling Methodsmentioning
confidence: 99%